Ocorrência de contaminação em carcaças bovinas durante o processamento em abatedouro frigorífico - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Refrigerated food safety products have as their main potential risk of microbiological contamination in carcass tissues, which occurs due to pathogenic microorganisms belonging to the natural microbiota of beef animals, found mainly in the gastrointestinal tract. Quality control is the main mechanism for monitoring microorganisms, as it not only offers a quality product, but promotes consumer health and well-being. The present study aimed to evaluate the sanitary efficiency of the production process through collections of cotton swabs and fresh meat, carrying out research on Salmonella, Enterobacteriaceaeand Escherichia colithrough microbiological analyzes according to normative recommendation No. 60, of December 20, 2018. During In carrying out the work, a total of 217 carcasses were evaluated for Enterobacteriaceaeand Salmonellaspp and 4 meat searches in the wild for analysis of Escherichia coli. As collections for analysis of enterobacteria were carried out in two stages, the first 5 swab samples per slaughter day, for 28 consecutive slaughters, making a total of 140 pieces. in the second, 5 samples of carcass swab were collected per week for 9 consecutive weeks, totaling 45 samples. At the end of the two stages, 185 dimensions were collected. For a survey of Salmonellaspp. 2 samples of swabs from semantic carcasses were collected for 16 consecutive weeks, totaling 32 samples. All the results found were favorable where no results are standard, thus concluding that the study studied has quality in its reduction process due to low prevalence of health indicators.
Keywords: Autocontrole; Carne; Contaminação; Micro-organismos; Self-control; Meat; Contamination; Microorganisms; CIENCIAS AGRARIAS